The Methodology of Pedagogical Action Research in Higher Education - Borozan, Maia; Bushnaq , Tatiana (Didactica Danubiensis, 2025)
Objectives: This study examines pedagogical action research (PedAR) methodology in higher education contexts, seeking to establish its operational definition while emphasizing both its pedagogical significance and the indispensable role of methodological adaptability in evidence-based educational inquiry. Prior Work: The investigation builds upon established educational research scholarship and PedAR’s epistemological traditions, while engaging with current discussions concerning methodological rigor. It specifically analyzes how structured professional training experiences can be effectively institutionalized within academic practice. Approach: The study conducts a theoretical analysis of how pedagogical action research (PedAR) literature conceptualizes qualitative, quantitative, and mixed-method approaches in higher education research. A critical review methodology underpins the development of a unified conceptual framework for PedAR. Results: The research proposes a reconceptualized PedAR model featuring systematic data triangulation, iterative analytical cycles, and hermeneutic interpretation. These components facilitate reflective academic practice and enable context-responsive refinement of pedagogical strategies across institutional environments. Implications: The findings provide actionable approaches for incorporating PedAR into faculty development programs and institutional research policies, empowering academic leaders and educators to foster enduring research-informed cultures. Value: Through its integrative and context-sensitive PedAR model, this study both consolidates the methodology’s foundations and validates its dual utility as a scholarly research approach and pedagogical enhancement tool in higher education.